CEO research in hospitality and tourism: a systematic literature review and future outlook - Saydam, Mehmet Bahri; Arici, Hasan Evrim; Koseoglu, Mehmet Ali (Routledge Journals, Taylor & Francis Ltd, 2024)
Although the literature on hospitality and tourism (H&T) emphasizes the role of the chief executive officer (CEO) in ensuring a firm's competitive advantage, little is known about how CEOs are deployed in H&T businesses. A significant gap in the research has been identified regarding how CEOs influence organizations in the sector. This study investigates potential synergies between H&T organizations' emphasis on CEOs and their impacts on various stakeholders. Research findings also show that CEO literature in H&T has largely focused on antecedents such as demographic, attitudinal, and organizational factors. Additionally, we suggest future research questions for CEO-related studies.
Keywords: Chief executive officer; future research agenda; firm performance; governance mechanism; hospitality and tourism; nomological network